Genome-Wide Characterization of Alternative Splicing Events and Their Responses to Cold Stress in Tilapia - Li, Bi Jun; Zhu, Zong Xian; Qin, Hui; Meng, Zi Ning; Lin, Hao Ran; Xia, Jun Hong (Frontiers in Genetics, 2020)
Alternative splicing (AS) is an important post-transcriptional regulatory mechanism for cells to generate transcript variability and proteome diversity. No systematic investigation of AS events among different tissues in response to stressors is available for tilapia currently. In this study, AS among different tissues was identified and the cold stress-related AS events were explored in a Nile tilapia (Oreochromis niloticus) line based on 42 RNA-seq datasets using a bioinformatics pipeline. 14,796 (82.76%; sd = 2,840) of the expression genes showed AS events. The two most abundant AS types were alternative transcription start site (TSS) and terminal site (TTS) in tilapia. Testis, brain and kidney possess the most abundant AS gene number, while the blood, muscle and liver possess the least number in each tissue. Furthermore, 208 differentially alternative splicing (DAS) genes in heart and 483 DAS in brain in response to cold stress. The number of AS types for alternative exon end, exon skipping and retention of single intron increased significantly under cold stress. GO enrichment and pathway overrepresentation analysis indicated that many DAS genes, e.g., genes in circadian clock pathway, may influence expression of downstream genes under cold stress. Our study revealed that AS exists extensively in tilapia and plays an important role in cold adaption.